Use of Olive Oil and Warm Water in Bathing Intervention in Preventing Risk of Skin Integrity Damage in Total Care Patients With Chronic Disease: A Case Study - Pele, Maria; Waluyo, Agung (Universitas Pendidikan Indonesia, 2019)
ABSTRACTChronic disease in total care patients can lead the damage of skin integrity. The skin integrity damage can be affected by various patient’s conditions, including physical immobilization, treatment, changes in skin turgor, immune decline, age, environmental changes and the effects of the diseases. Its can make the complications of patient condition such as infection so that can causes the longer length of stay and higher of hospitalization costs. The aim of this paper is to identified use of olive oil and warm water in bathing intervention in preventing risk of skin integrity damage in total care patients with chronic disease. This is a case study in one total care patient with chronic disease. Skin integrity assesed by Braden score and patient condition assesed by reseacher observations. Bathing the patient using olive oil and warm water has a calming effect on the patient and preventing damage to the integrity of the skin. Use of olive oil and warm water in bathing intervention can preventing risk of skin integrity damage in total care patients with chronic disease.ABSTRAKPenyakit kronis pada pasien dengan perawatan total dapat menyebabkan kerusakan integritas kulit. Kerusakan integritas kulit dapat dipengaruhi oleh berbagai kondisi pasien, termasuk imobilisasi fisik, perawatan, perubahan turgor kulit, penurunan kekebalan, usia, perubahan lingkungan dan efek penyakit. Hal ini dapat menyebabkan komplikasi pada kondisi pasien seperti infeksi sehingga dapat menyebabkan lama hari rawat lebih lama dan biaya rawat inap yang lebih tinggi. Tujuan dari tulisan ini adalah untuk mengidentifikasi penggunaan minyak zaitun dan air hangat dalam intervensi memandkani dalam mencegah risiko kerusakan integritas kulit pada pasien perawatan total dengan penyakit kronis. Ini adalah studi kasus pada satu pasien perawatan total dengan penyakit kronis. Integritas kulit dinilai oleh Braden score dan kondisi pasien dinilai dengan pengamatan peneliti. Memandikan pasien dengan minyak zaitun dan air hangat memiliki efek menenangkan pada pasien dan mencegah kerusakan integritas kulit. Penggunaan minyak zaitun dan air hangat dalam intervensi mandi dapat mencegah risiko kerusakan integritas kulit pada pasien perawatan total dengan penyakit kronis.